Ginsenoside Rg3 inhibits keloid fibroblast proliferation, angiogenesis and collagen synthesis in vitro via the TGF-β/Smad and ERK signaling pathways - Tang, Mengyao (Int J Mol Med, 2018)
A wide range of therapeutic options exists for the treatment of keloids, all of which have their own strengths; however, a high risk of side-effects and frequent recurrence remains. Therefore, the present study aimed to identify improved therapeutic approaches or drugs for the treatment of keloids. Ginsenoside Rg3 (Rg3) has been reported to exert numerous antitumor effects, thus indicating that Rg3 may be a potential therapeutic agent that targets keloids. The present study determined the effects of Rg3 on human keloid fibroblasts (KFs) in vitro, and further explored the associated molecular and cellular mechanisms. Keloid scar specimens were obtained from patients, aged between 22 and 35 years, without systemic diseases and primary cells were isolated from keloid tissues. In each assay, KFs were divided into three groups and were cultured in medium with or without various concentrations of Rg3 (50 or 100 μg/ml). Cell viability assay, flow cytometry, quantitative polymerase chain reaction, cell migration assay, immunofluorescence staining, western blot analysis, Transwell cell invasion assay and immunohistochemical analysis were used to analyze the KFs and keloid explant cultures. The results of the present study demonstrated that Rg3 was able to exert an inhibitory effect on the transforming growth factor-β/Smad and extracellular signal-regulated kinase signaling pathways in KFs. The proliferation, migration, invasion, angiogenesis and collagen synthesis of KFs were markedly suppressed following treatment with Rg3. Furthermore, the results of an ex vivo assay indicated that Rg3 inhibited angiogenesis and reduced collagen accumulation in keloids. Significant statistical differences existed between the control and Rg3-treated groups (P<0.05). All of these experimental results suggested that Rg3 may serve as a reliable drug for the treatment of patients with keloids.